2020
DOI: 10.1039/c9ra08599h
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments on oximes to improve the blood brain barrier penetration for the treatment of organophosphorus poisoning: a review

Abstract: Organophosphorus (OP) compounds are highly toxic synthetic compounds which have been used as pesticides and developed as warfare nerve agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…5 Unlike the OPs, oximes generally have a low degree of penetration through the BBB, because of which they have little to no ability to reactivate brain AChE. 7 Knowing that central respiratory depression is a main cause of death in OP intoxication, 8,9 when researching a new oxime, it is very important to determine the degree of its penetration through the BBB. Finding an oxime that is more penetrable, would mean a greater therapeutic success.…”
Section: The Marinković-maksimović Methods (Mm Method)mentioning
confidence: 99%
“…5 Unlike the OPs, oximes generally have a low degree of penetration through the BBB, because of which they have little to no ability to reactivate brain AChE. 7 Knowing that central respiratory depression is a main cause of death in OP intoxication, 8,9 when researching a new oxime, it is very important to determine the degree of its penetration through the BBB. Finding an oxime that is more penetrable, would mean a greater therapeutic success.…”
Section: The Marinković-maksimović Methods (Mm Method)mentioning
confidence: 99%
“…However, none of them are yet to be manufactured. New oxime's structure, uncharged oximes, conjugation of uncharged oximes, and sugar-oxime moieties are among several strategies to increase the BBB penetration efficiency of oximes [61]. It has been reported that oximes get access into the brain and, thus, reactivate inhibited local AChE.…”
Section: Limitations Of Oximementioning
confidence: 99%
“…Another promising approach is to apply specific BBB transporters such as P-glycoprotein (Pgp) inhibitors and nanoparticles as drug carrier which has also been reported [120]. Due to the inadequate reports focused on the application of these approaches for oximes, the Pgp inhibitors and nanomaterial carriers for oxime delivery into the CNS need to be further studied in the future [61].…”
Section: Future Directions In the Treatment Of Op Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…The large scale repeated use of nerve agents during the Iran-Iraq war in the 1980s against civilians by Iraqi troops, and during terrorist attacks by the Aum Shinrikyo sect in Japan [14], emphasize the constant threat and urgent Severe pain in exposed area, gastrointestinal distress, vomiting, cardiac arrhythmias need for the development of sensitive and specific diagnostic tools for CWA. In fact, simple synthesis and high toxicity [15] are the major reasons that have led to the significant use of these chemical materials during various wars, for example in Syria 2017, and for individual assassinations -February 2017 in Kuala Lumpur [16][17][18][19]. The rapid detection of these toxic agents in the environment, public places or workplaces and the monitoring of an individual's exposure to CWA become increasingly vital for homeland security and environment monitoring.…”
mentioning
confidence: 99%